2016 Laboratory guidelines for postvasectomy semen analysis: Association of Biomedical Andrologists, the British Andrology Society and the British Association of Urological Surgeons. Issue 7 (15th April 2016) - Hancock, P; Woodward, B J; Muneer, A; Kirkman-Brown, J C
Abstract : Post-vasectomy semen analysis (PVSA) is the procedure used to establish whether sperm are present in the semen following a vasectomy. PVSA is presently carried out by a wide variety of individuals, ranging from doctors and nurses in general practitioner (GP) surgeries to specialist scientists in andrology laboratories, with highly variable results. Key recommendations are that: (1) PVSA should take place a minimum of 12 weeks after surgery and after a minimum of 20 ejaculations. (2) Laboratories should routinely examine samples within 4 h of production if assessing for the presence of sperm. If non-motile sperm are observed, further samples must be examined within 1 h of production. (3) Assessment of a single sample is acceptable to confirm vasectomy success if all recommendations and laboratory methodology are met and no sperm are observed. Clearance can then be given. (4) The level for special clearance should be <100 000/mL non-motile sperm. Special clearance cannot be provided if any motile sperm are observed and should only be given after assessment of two samples in full accordance with the methods contained within these guidelines. Surgeons are responsible both preoperatively and postoperatively for the counselling of patients and their partners regarding complications and the possibility of late recanalisation after clearance. These 2016 guidelines replace the 2002 British Andrology Society (BAS) laboratory guidelines and should be regarded as definitive for the UK in the provision of a quality PVSA service, accredited to ISO 15189:2012, as overseen by the United Kingdom Accreditation Service (UKAS).